2011
DOI: 10.1016/j.ydbio.2011.05.660
|View full text |Cite
|
Sign up to set email alerts
|

Pou5f1 contributes to dorsoventral patterning by positive regulation of vox and modulation of fgf8a expression

Abstract: Pou5f1/Oct-4 in mice is required for maintenance of embryonic pluripotent cell populations. Zebrafish pou5f1 maternal-zygotic mutant embryos (spiel ohne grenzen; MZspg) lack endoderm and have gastrulation and dorsoventral patterning defects. A contribution of Pou5f1 to the control of bmp2b, bmp4 and vox expression has been suggested, however the mechanisms remained unclear and are investigated in detail here. Low-level overexpression of a Pou5f1-VP16 activator fusion protein can rescue dorsalization in MZspg m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 84 publications
(130 reference statements)
4
40
1
1
Order By: Relevance
“…The involvement of pou2 in DV patterning was previously reported based on the analyses of M-and/or Z-spg mutants (Reim and Brand, 2006) and the effects of mRNA injection (Belting et al, 2011). In the present study we further showed that pou2 is also involved in CE movement.…”
Section: Establishment Of a Transgenic (Tg) Fish Line Harboring An Insupporting
confidence: 87%
See 1 more Smart Citation
“…The involvement of pou2 in DV patterning was previously reported based on the analyses of M-and/or Z-spg mutants (Reim and Brand, 2006) and the effects of mRNA injection (Belting et al, 2011). In the present study we further showed that pou2 is also involved in CE movement.…”
Section: Establishment Of a Transgenic (Tg) Fish Line Harboring An Insupporting
confidence: 87%
“…An active and repressive form of pou2 was recently reported to cause ventralization and dorsalization, respectively, by mRNA injection (Belting et al, 2011), although the activity of wild-type pou2 was not addressed directly. In the present study, we first sought to reexamine the effects of wild-type pou2 as compared with those of active and repressive pou2 by mRNA injection.…”
Section: 1mentioning
confidence: 99%
“…Expansion of gsc at sphere stage shows that dorsoventral patterning is altered prior to the first observable morphological defects in split top mutants. Although not observed in BMP pathway mutants, a similar expansion of dorsal midline mesoderm is observed in other maternal-effect dorsalized mutants, including ints6 (Kapp et al, 2013) and maternal-zygotic (MZ) pou5f3 (formerly pou5f1 or oct4) (Belting et al, 2011;Reim and Brand, 2006).…”
Section: Maternal-effect Split Top Embryos Exhibit Morphogenesis and mentioning
confidence: 61%
“…Pou5f3 in the embryo acts as an activator of gene expression determining ventral fates by direct activation of the Vox promoter, and this is a phylogenetically conserved mechanism. In wild type embryos, the Vox expression was enhanced by the Pou5f3, but it was partially suppressed in the mutants (10). However,…”
Section: Introductionmentioning
confidence: 92%